Toxin‐Enabled "On‐Demand" Liposomes for Enhanced Phototherapy to Treat and Protect against Methicillin‐Resistant Staphylococcus aureus Infection. Issue 35 (20th July 2022) - Zhuge, Deli; Chen, Mengchun; Yang, Xuewei; Zhang, Xufei; Yao, Lulu; Li, Li; Wang, Haonan; Chen, Hao; Yin, Qingqing; Tian, Dongyan; Weng, Cuiye; Liu, Shuangshuang; et al.
Abstract: An effective therapeutic strategy against methicillin‐resistant Staphylococcus aureus (MRSA) that does not promote further drug resistance is highly desirable. While phototherapies have demonstrated considerable promise, their application toward bacterial infections can be limited by negative off‐target effects to healthy cells. Here, a smart targeted nanoformulation consisting of a liquid perfluorocarbon core stabilized by a lipid membrane coating is developed. Using vancomycin as a targeting agent, the platform is capable of specifically delivering an encapsulated photosensitizer along with oxygen to sites of MRSA infection, where high concentrations of pore‐forming toxins trigger on‐demand payload release. Upon subsequent near‐infrared irradiation, local increases in temperature and reactive oxygen species effectively kill the bacteria. Additionally, the secreted toxins that are captured by the nanoformulation can be processed by resident immune cells to promote multiantigenic immunity that protects against secondary MRSA infections. Overall, the reported approach for the on‐demand release of phototherapeutic agents into sites of infection could be applied against a wide range of high‐priority pathogens. Abstract : Van‐Lipo(IR780)‐PFC can capture MRSA toxins in situ, resulting in the on‐demand release of phototherapeutic agents, thus improving the specificity of PTT/PDT under NIR irradiation. Meanwhile, pore formation upon the insertion of toxins into the nanoparticles not only attenuating toxins' cytotoxicity, but also resulting in generation of vaccines in situ, thus leading to anti‐MRSA immune response for preventing subsequent infection.